(untitled) (World Economics and Finance Bulletin, 2022)
In the article isdiscussed the ways of Islamic financial instruments usingin commercial banks, as well analysis of its advantages and prospects for development. The article also presents the existing problems in the Islamic financial instruments in the activities of commercial banks of the Republic of Uzbekistan, as well as the author’s approaches and proposals for their solution and prospects for theseimplementation development.